Optimizing intercropping of sweet corn and groundnut yield and economic assessment - Abdul Haya, Borhan; Sulaiman, Zulkefly; Ramlan, Mohd Fauzi; Ariffin, Mohd Rizal; Mohammad Yusoff, Martini; Tsan, Fui Ying; Kalam, Mohamad Asrol; Abd Karim, Khairul Najmuddin; Zaheid, Muhammad Iz’aan Izzuddin (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Intercropping is a cost-effective strategy for enhancing agricultural productivity under conditions of limited land availability and increasing food demand. This study evaluated the biological, competitive, and economic performance of a sweet corn–groundnut intercropping system using the Land Equivalent Ratio (LER), Aggressivity Index (AI), and Monetary Advantage Index (MAI). Field experiments were conducted under three cropping regimes: sweet corn monoculture (T1), groundnut monoculture (T2), and intercropping treatments (T3, T4, T5). The intercropping involved strip planting with different sowing times: simultaneous planting (T3), groundnut sown two weeks before sweet corn (T4), and sweet corn sown two weeks before groundnut (T5). Findings revealed that sweet corn monoculture (T1) consistently outperformed intercropping in terms of profitability, largely due to market pricing based on ears rather than weight, which favored corn sales. The T4 system achieved the highest LER, reflecting better land-use efficiency, while the Aggressivity Index (AI), Competitive Ratio (CR), Relative Crowding Coefficient (RCC), and Actual Yield Loss (AYL) confirmed the dominance of corn in intercropping arrangements. However, the Area Time Equivalent Ratio (ATER) remained below 1, suggesting no temporal advantage over monocropping systems. Positive values of CR, RCC, and AYL further confirmed corn dominance in intercropping. The highest MAI was observed in T4, indicating potential economic benefits, but sweet corn monoculture (T1) remained more profitable. Additionally, plant density was higher in monoculture than in intercropped plots. Overall, while intercropping improved land-use efficiency, sweet corn monoculture provided greater profitability for smallholder farmers under the tested conditions.